O-083 Tumors of the central nervous system among women treated with fertility drugs: a population-based cohort study. (30th June 2022) - Frandsen, C L B; Jensen, A; Poulsen, F R; Møller, M; Albieri, V; Lindquist, S; Nøhr, B; Kjær, S K
Abstract: Study question: Is the use of fertility drugs among infertile women associated with tumors of the central nervous system (CNS)? Summary answer: The use of most specific types of fertility drugs is not associated with an increased risk of CNS tumors overall. What is known already: Few previous studies have investigated the association between fertility drugs and CNS tumors. Studies have reported inconsistent results regarding the risk of CNS tumors associated with assisted reproductive technologies such as in vitro fertilization (IVF). No studies have reported the risk associated with various specific fertility drugs. Study design, size, duration: Retrospective population-based cohort study of all women included in the Danish Infertility Cohort. The study cohort consisted of 148 016 infertile women after exclusion of women who emigrated, died, were diagnosed with cancer before infertility diagnosis, and women for whom information on level of education was missing. The cohort was linked to various national health- and civil registers to study all 20- to 45-year old infertile women in Denmark during 1995-2017. Participants/materials, setting, methods: The study cohort was linked to various national health and population registers to obtain information on fertility drugs (clomiphene citrate, gonadotropins, human chorionic gonadotropin, gonadotropin-releasing hormone receptor modulators and progesterone), CNS tumors, relevant covariates and vital and emigration status. Cox proportional hazard regression models were used to calculate hazard ratios and 95% confidence intervals for CNS tumors overall and for gliomas, meningiomas and diverse benign tumors of the brain and other parts of the CNS. Main results and the role of chance: During a median 11.3 years of follow-up, 328 women were diagnosed with a CNS tumor. No marked associations were observed between use of most types of fertility drugs (clomiphene citrate, gonadotropins, gonadotropin releasing hormone receptor modulators and progesterone) and CNS tumors. However, ever use of human chorionic gonadotropin was associated with an increased rate of gliomas (HR 2.13 95% CI 0.90-5.01) but a decreased rate of meningiomas (HR 0.49 95% CI 0.28-0.87). No clear associations with CNS tumors were observed according to time since first use or cumulative dose for any specific fertility drugs. Additional studies with longer follow-up are necessary to support these findings. Limitations, reasons for caution: The median age at end of follow-up (43.5 years) was lower than the median age for CNS tumors diagnosis (60 years). Information on estrogen use, treatment regimens and number of cycles is only partly available in the registers and these were not included in this study. Wider implications of the findings: This study presents reassuring results regarding the risk of tumors of the CNS among women treated with fertility drugs. Our study is only generalizable to premenopausal women, and the risk for postmenopausal women remains to be assessed. Trial registration number: not applicable